Lethal concentration 50 (LC50) and effects of diuron on morphology of brine shrimp Artemia salina (Branchiopoda: Anostraca) nauplii - Mohamed Abu Shaala, Najla; Zulkifli, Syaizwan Zahmir; Ismail, Ahmad; Azmai, Mohammed Noor Amal; Mohamat-Yusuff, Ferdaus (Elsevier, 2015)
Diuron is an alternative biocide to replace tributyltin in antifouling paints. However, its effect on non-targeted organisms are not fully studied, hence this study was conducted to investigate toxicological effects of Diuron in the early life stage (24hr post-hatch nauplii) of brine shrimp Artemia salina. The lethal concentration 50 (LC50) of Diuron on A. salina nauplii was determined after 24 hours, 48 hours and 72 hours exposure after conducting a range definitive tests. Additional investigations on morphological abnormalities and total length were also conducted. Results showed that LC50 of Diuron were 23.27 mg.L-1, 12.19 mg.L-1, 6.00 mg.L-1 in 24, 48 and 72 hours, respectively. Some external abnormalities were also observed. The total length was found to decrease with the increase in Diuron concentration. These results indicate that Diuron is an environmentally toxic substances. Furthermore, in-depth investigation should be conducted to establish A. salina as a bioindicator for Diuron contamination